Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T20:45:53+01:00
A) (2a-3)+4a-9-(-7a-16)=
=2a-3+4a-9+7a+16=13a+4
dla a=-2
(13×-2)+4=-22
b)x-[-x-(1-x)-(-x+1)]=
=x-[-x+1+x+x-1]=
=x+x-1-x-x+1=0
c)(2a+3b)-(6b-4a)-(7a-10b)=
=2a+3b-6b+4a-7a+10b=-a+7b
dla a=2 b=-2
-2+(7×-2)=-16

nie wiem czy oto Ci chodziło, bo nie wytłumaczyłeś do końca:D
2009-11-23T20:45:55+01:00
A)(2a-3)+4a-9-(-7a-16) a=-2
(2a-3)+4a-9-(-7a-16) = 2a-3+4a-9+7a-16= 13a+4=13*-2+4=-26+4=-22

b)x-[-x-(1-x)-(-x+1)] x=-1
x-[-x-(1-x)-(-x+1)]=x-[-x+1+x+x-1]=x+x-1-x-x+1=0

c)(2a+3b)-(6b-4a)-(7a-10b) a=2 b=-2
(2a+3b)-(6b-4a)-(7a-10b)=2a+3b-6b+4a-7a+10b=-a+7b=-2+(7×-2)=-16

d)x-(x-(x-(x-(x-(x-1)-1)-1)-1)-1) x=-4
d)x+x+x+x+x+x+1+1+1+1+1= 6x+5=6*-4+5= -24+5=-19 (nie wiem czy dobrze)
2009-11-23T20:58:29+01:00
A) (2a-3)+4a-9-(-7a-16)= 2a-3+4a-9+7a+16= 13a+4= -26+4= -22
b) x-[-x(1-x)-(-x+1)]=x-[-x+x²+x-1]=x-(x²-1)=x-x²+1=-1+1+1=2
c)(2a+3b)-(6b-4a)-(7a-10b)= 2a+3b-6b+4a-7a+10b=-a-7b=-2-(7*-2)=-2+14=12
d( x-(x-(x-(x-(x-(x-1)-1)-1)-1)-1)-1= x-(x-(x-(x-(x-x+1-1)-1)-1)-1)-1=
= x-(x-(x-(x+1)-1)-1)-1=x-(x-(x-x-1-1)-1)-1=x-(x+1)-1=x-x+1-1=0